2013
DOI: 10.1002/pbc.24453
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characteristics of a pancreatic adenocarcinoma associated with Shwachman‐Diamond syndrome

Abstract: Our case raises the possibility that solid tumors are associated with SDS, thereby broadening the clinical phenotype of the disease. The relatively young age at cancer diagnosis and the specific involvement of the pancreas make the possibility of an association with SDS likely. Similar to leukemia in SDS, the pancreatic cancer developed in hypoplastic tissues. This observation and the relative genomic stability of the tumor strengthen the hypothesis of improved adaptation of malignant clones among a population… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
1
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 40 publications
1
20
1
1
Order By: Relevance
“…7): (1) ASIC2 acid sensing ion channel 2, (2) GABRE—gamma-aminobutyric acid A receptor, epsilon, (3) LINC00525—long intergenic non-protein coding RNA 525, (4) CTNNA3—catenin alpha 3. The CTNNA3 gene has been shown to be linked to the Shwachman-Diamond syndrome which is characterized by a high risk of leukaemia [31]. In terms of relation to the bone marrow processes the GABRE gene which is a gammaaminobutyric acid receptor has proved to play a role during bone marrow stromal cell transplantation in the injured spinal cord in mice [32].…”
Section: Resultsmentioning
confidence: 99%
“…7): (1) ASIC2 acid sensing ion channel 2, (2) GABRE—gamma-aminobutyric acid A receptor, epsilon, (3) LINC00525—long intergenic non-protein coding RNA 525, (4) CTNNA3—catenin alpha 3. The CTNNA3 gene has been shown to be linked to the Shwachman-Diamond syndrome which is characterized by a high risk of leukaemia [31]. In terms of relation to the bone marrow processes the GABRE gene which is a gammaaminobutyric acid receptor has proved to play a role during bone marrow stromal cell transplantation in the injured spinal cord in mice [32].…”
Section: Resultsmentioning
confidence: 99%
“…DNA quantitative real-time PCR (DNA-qPCR) was performed using Power SYBR Green (Applied Biosystems, Warrington, UK) as described,30 with primers designed within the PARN deletion regions, and FOXP2 as a reference gene (see online supplementary table S2).…”
Section: Methodsmentioning
confidence: 99%
“…An increase in Fas‐mediated apoptosis is also seen, presumably leading to bone marrow failure . A recent study demonstrated the possibility that pancreatic tumors may be associated with SDS, thereby broadening the clinical phenotype of the disease . In vivo SDS models based on mammals, insects, and fish replicate the genetic and/or developmental aspects of ribosomopathies, and have led to the identification of pathways and candidate molecules that are important in the pathogenesis of the diseases.…”
Section: Ribosomal Proteins and The Pathogenesis Of Human Diseasesmentioning
confidence: 99%